Toward the Role of Teacher Caring and Teacher-Student Rapport in Predicting English as a Foreign Language Learners’ Willingness to Communicate in Second Language - Song, Lili; Luo, Runfeng; Zhan, Qiqi (Frontiers in Psychology, 2022)
Following the advent of positive psychology (PP), positive communication behaviors have been studied as significant predictors of language learners’ willingness to communicate in second language (L2WTC). Yet, the role of two important communication behaviors, namely teacher caring and teacher-student rapport, in predicting EFL learners’ L2WTC has remained elusive. To address this gap, this investigation assessed the impact of teacher caring and teacher-student rapport on Chinese EFL learners’ L2WTC. To do so, 4392 Chinese EFL learners were invited to answer three reliable questionnaires. Performing Spearman correlation analysis, favorable relationships were found among the variables. Multiple regression analysis was also conducted to inspect the potential of teacher caring and teacher-student rapport in predicting Chinese EFL learners’ L2WTC. The outcomes of multiple regression analysis indicated that Chinese EFL learners’ L2WTC can be substantially predicted by teacher caring behaviors and teacher-student rapport. The implications and limitations of the findings are also discussed.